The ancient kazakh legends in the drama of euripides of scholarly writers - Assel Toktanova, Anar Sadyrova, Irina Chsherbovskikh, Muratbek Imangazinov, Bakyt Esimkulov, (Opción, 2019)
The article reflects the ancient Kazakh legends in the drama of Euripides on the translation of scholarly writers of the ХІХ-ХХ centuries via comparative qualitative research methods. As a result, a historical drama in our day is usually based upon a considerable study of the period and characters dramatized. In conclusion, this was natural for Euripides and Korkut, for they seem to have been endowed with sufficient mental balance to laugh at things without ceasing to respect them, to see the funny side of their own beliefs.